Obstetric and perinatal outcomes of pregnancies Following Assisted Reproductive Techniques In a Tertiary Care Center Compared with Age Matched Control Conceived Spontaneously. - Kumari, Ruchi; Patel, Anubhuti; Chanania, Kabita (Journal of Neonatal Surgery, 2025)
Background: Infertility is a growing global health issue, affecting millions of couples worldwide. Assisted Reproductive Technology (ART) has revolutionized infertility treatment, yet concerns remain regarding its impact on maternal and neonatal outcomes. Pregnancies conceived through ART may be associated with higher risks of complications such as hypertensive disorders, gestational diabetes mellitus (GDM), preterm birth, and neonatal intensive care unit (NICU) admissions compared to spontaneous conceptions (SC). Objective: This study aimed to compare the obstetric and perinatal outcomes of pregnancies conceived via ART with age-matched pregnancies conceived spontaneously in a tertiary care center in Eastern India. Materials and Methods: A prospective observational study was conducted at IMS and SUM Hospital, Bhubaneswar, India, over 18 months. A total of 286 pregnant women aged 21–40 years were included, with 221 conceiving spontaneously and 65 through ART (31 via intrauterine insemination [IUI] and 34 via in vitro fertilization/intracytoplasmic sperm injection [IVF/ICSI]). Data on maternal demographics, pregnancy complications, delivery outcomes, and neonatal health were analyzed using SPSS software. Statistical significance was set at p ≤ 0.05. Results: ART pregnancies were associated with significantly higher rates of maternal complications, including gestational hypertension (15.03% vs. 7.2%; p=0.01), GDM (1.74% vs. 0.9%; p=0.04), and preterm birth (21.67% vs. 12.1%; p=0.001). ART pregnancies also had a higher rate of cesarean section (16% vs. 8.2%; p=0.002) and NICU admissions (18.3% vs. 9.8%; p=0.002). Additionally, postpartum depression was more frequent in the ART group (5.3% vs. 2.1%; p=0.04). Conclusion: This study highlights the increased risk of maternal and neonatal complications in ART pregnancies compared to spontaneous conceptions. Enhanced prenatal surveillance, individualized care strategies, and psychological support are crucial for improving ART pregnancy outcomes. Further large-scale studies with long-term follow-ups are needed to understand the broader implications of ART on maternal and neonatal health.